Second language distance learning and teaching : theoretical perspectives and didactic ergonomics - Bertin, Jean-Claude, 1955-; Grave, Patrick, 1955-; Narcy-Combes, Jean-Paul, 1947- (Hershey, PA : Information Science Reference, 2010)
'This book problematizes the construct of distance second language learning, in order to see what it covers, if its parameters are well-defined, what theories can guide the actions of the participants, and whether a model of action can be suggested with a method to validate the model'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Second language acquisition -- Computer-assisted instruction; Language and languages -- Computer-assisted instruction; English language -- Study and teaching -- Foreign speakers; English language -- Computer-assisted instruction for foreign speakers; Internet in education